2004
DOI: 10.1111/j.1523-1755.2004.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antioxidant enzymes in murine podocytes precedes injury by puromycin aminonucleoside

Abstract: These results demonstrate that (1) PAN treatment induces significant early changes in podocyte ROS, (2) podocytes can mount an antioxidant defense against oxidant stress, and (3) this protective response is initiated prior to the development of extensive oxidant-induced podocyte structural injury. These findings suggest that enhancement of podocyte AOE activities represent a potential therapeutic target to protect from or ameliorate podocyte injury during nephrotic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
2
33
1
Order By: Relevance
“…6B). As shown previously (16), there was no indication of overall cell death at the 48-h time point in PAN-treated cells (data not shown).…”
Section: Transduction Of Tat-neph1cd Protects Podocytes From Panand Asupporting
confidence: 53%
See 3 more Smart Citations
“…6B). As shown previously (16), there was no indication of overall cell death at the 48-h time point in PAN-treated cells (data not shown).…”
Section: Transduction Of Tat-neph1cd Protects Podocytes From Panand Asupporting
confidence: 53%
“…7, A and B). Cytoskeleton changes similar to PAN, such as increase in stress fibers close to the cell periphery (16,36) and gradual loss of Neph1 from the junctions, were noted in the Ang II-treated cells. In contrast, the distribution of Neph1 at the junctions was significantly higher (p Ͻ 0.05) in TAT-Neph1CD-transduced podocytes as compared with the untransduced cells (Fig.…”
Section: Transduction Of Tat-neph1cd Protects Podocytes From Panand Amentioning
confidence: 91%
See 2 more Smart Citations
“…It is very interesting that mRNA expression of SV2B is already dramatically downregulated 1 h after PAN administration and was recovered at the peak of proteinuria. Although the initiation mechanism of PAN nephropathy is uncertain, it has been reported that PAN treatment induces significant early changes in reactive oxygen species in podocyte (37). The downregulation of SV2B might be mediated by reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%